Answer:
3:9:24
Step-by-step explanation:
<u>Answer</u>:
Jared is right.
<u>Explanation</u>:
proof 1:
10 - 4 = 6
6 = 6
second proof:
10-3 - 4 = 6 - 3
10 - 7 = 3
3 = 3
third proof:
10 - 4 - 3 = 6 - 3
10 - 7 = 3
3 = 3
Hence for all LHS = RHS proved and Jared is correct.
Expanded Form:
40,000,000+4,000,000+80,000+700
Answer:
The third expression: (2x)^3
Step-by-step explanation:
Plug in 3 for x in each expression
2x^3
2(3)^3
Use PEMDAS
2 (3 × 3 × 3)
2 (9 × 3)
2 (27)
54
2x^3 + 5
(The last expression told us 2x^3 = 54 so feel free to use this information to make life easier)
54 + 5
59
(2x)^3
(2 × 3)^3
Use PEMDAS
6^3
6 × 6 × 6
36 × 6
216
(x - 1)^3
(3 - 1)^3
Use PEMDAS
2^3
2 × 2 × 2
4 × 2
8
216 is the greatest value so the third expression is the answer
Answer:
We can use quadratic formula
a=3, b= -1, c=4
Step-by-step explanation: